(untitled) (Indonesian Journal of Agrarian Law, 2026)
This study examines a dispute over public and social facility land in the Bawen City Land housing estate, Semarang Regency, affected by land acquisition for the Bawen–Yogyakarta Toll Road. Parcels designated in the ratified site plan as a prayer hall, a parking area, and a well and water reservoir were registered as freehold title in the developer director’s personal name, encumbered as security for debt, never handed over to the regional government, and ultimately became the basis for receiving compensation. Two problems are formulated: the legal status of those land rights in light of the handover obligation and the social function of land, and the reading of the entitled party norm that yields substantive justice. The study applies a normative juridical method with statutory, conceptual, and case approaches, drawing on legislation, Decision Number 8/Pdt.G/2024/PN Unr, and legal literature, reinforced by testimony from affected residents. The findings show that the developer’s conduct satisfies the elements of circumvention of the law, because formally valid legal forms were deployed to evade a mandatory obligation, producing illusory certainty that is flawless on paper yet negates the social function of land. It argues that the right to receive compensation is not identical to the right to enjoy it unencumbered, because substitute money inherits the designation of the object it replaces, so the handover obligation converts into an obligation to provide equivalent replacement facilities. Its novelty is a four-stage function restoration model placing regional government as the principal actor.